2014
DOI: 10.1123/jsep.2013-0218
|View full text |Cite
|
Sign up to set email alerts
|

Can Persuasive Messages Encourage Individuals to Create Action Plans for Physical Activity?

Abstract: Given the positive influence of action planning on physical activity, persuasive messages could be designed to promote action planning. The purpose of this paper was to test action planning messages in two studies. Participants were allocated to one of two message groups, reading either a physical activity only or physical activity plus action planning message (Study 1) and either a gain-framed or loss-framed action planning message (Study 2). The percent of individuals who created an action plan and the quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Therefore, such messages could especially target this group, for example, by leveraging on the fact that in natural environments people would encounter others who, like them, are not necessarily as motivated to do more structured forms of exercise. If framed in the correct way, these messages could persuade people to set specific plans of action for physical activity [41]; a known method of bridging the gap that sometimes exists between motivation and action [42]. …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, such messages could especially target this group, for example, by leveraging on the fact that in natural environments people would encounter others who, like them, are not necessarily as motivated to do more structured forms of exercise. If framed in the correct way, these messages could persuade people to set specific plans of action for physical activity [41]; a known method of bridging the gap that sometimes exists between motivation and action [42]. …”
Section: Discussionmentioning
confidence: 99%
“…Some experimental evidence from studies comparing gain-and loss-framed message content in trial designs have found no significant difference in effectiveness on proximal or distal outcomes in young adults [55][56][57][58], adults over 55 years [56], inactive colorectal cancer survivors [59], or in community dwelling individuals with multiple sclerosis [60]. However, an advantage for gain-framed messages over loss-framed messages has been found in general adult populations [10,61,62], university students [63], overweight females [64], sedentary adults [65], and cardiac rehabilitation patients [66] on outcomes including attitude, exercise intentions and PA behaviour. It also appears the effect of framing may depend on the type of outcome emphasised and on the individual's need for cognition (i.e.…”
Section: Message Contentmentioning
confidence: 99%
“…In the present study, walking brochures lacked general and normative information about PA for health, behavioural prompts and efficacy information (especially content encouraging general walking behaviours). Messages containing such information can be effective in motivating inactive people to set better plans to undertake PA (Sweet et al , 2014). Most brochures and much of the content therein, whether intentionally or not, was therefore intended for people who already do recreational walking in the natural environment.…”
Section: Discussionmentioning
confidence: 99%